Long term earnings inequality, earnings instability and temporary employment in Spain: 1993 - 2000 - María Cervini Plá; Xavier Ramos (Institute for the Study of Labor (IZA), 2008)
This paper provides a longitudinal perspective on changes in Spanish male earnings inequality for the period 1993-2000, by decomposing the earnings covariance structure into its permanent and transitory parts. According to the Spanish sample of the European Community Household Panel, cross-sectional earnings inequality of male full-time employees falls over the second half of the Nineties. The longitudinal analysis shows that such decline was determined by a decrease in earnings instability and an increase of the permanent earnings component. Given the marked decline in temporary employment over the sample period, we also examine the effect of the type of contract on earnings variance components, and we find that workers with fixed-term contract have on average more instability than workers with permanent contract. This evidence suggests that the decline in temporary employment is responsible for the decreasing earnings instability.
urn:nbn:de:101:1-20080613112
Keywords: C23; 330; Earnings dynamics; permanent and transitory differences; earnings instability; covariance structure; minimum distance; temporary employment; Spain; Lohnstruktur; Einkommensverteilung; Risiko; Befristeter Arbeitsvertrag; Arbeitsverhältnis; Spanien